Pelatihan Teknologi Berbasis Aplikasi Web: Membantu Tenaga Kerja Meningkatkan Kompetensi dan Daya Saing - Ridian Gusdiana; Ridwan Setiawan; Muhammad Farhan (Jurnal Algoritma, 2023)
Errors in recruiting prospective employees can have an impact on company performance, prospective employees who are recruited need to prove their abilities and expertise. The purpose of this research is to design an integrated and easily accessible web-based prospective employee training information system that can help improve the skills of prospective employees who will be recruited. The research method used is the Rational Unified Process (RUP) with the stages of Inception, Elaboration, Construction, and Transition with system modeling using the Unified Modeling Language (UML), namely UseCase Diagrams, Activity Diagrams, Sequence Diagrams, and Class Diagrams. This research resulted in a system design and Web-Based Candidate Training Information System with available features including information on training data, training registration data, training materials, assignment assessments, and training management. This research was conducted at one of the service companies in information technology in Garut Regency, namely CV. Asgardian Techno Service. Using an information system for prospective employee training is made into a solution for companies to improve the quality of employees through training that can be accessed by both participants, mentors and decision makers.